Belatacept for prevention of acute rejection in adult patients who have had a kidney transplant: an update - Wojciechowski D (Dove Medical Press, 2012)
David Wojciechowski, Flavio VincentiKidney Transplant Service, University of California, San Francisco, CA, USAAbstract: In June 2011, the US Food and Drug Administration approved belatacept for the prophylaxis of organ rejection in adult kidney transplant recipients. This review discusses the use of belatacept for the prevention of acute rejection as part of a maintenance immunosuppression regimen. Belatacept is a selective costimulation blocker designed to provide effective immunosuppression while avoiding the toxicities associated with calcineurin inhibitors. Phase III trial data have demonstrated that belatacept is noninferior to cyclosporine in 1-year patient and allograft survival. Three-year data demonstrate an ongoing improvement in mean measured glomerular filtration rate in belatacept-treated versus cyclosporine-treated patients. However, the rate of acute rejection was higher in belatacept-treated patients compared with cyclosporine. Specifically, there was a higher incidence of Banff type II rejections in patients treated with belatacept. Despite the higher Banff grade, rejections on belatacept were not associated with other factors associated with poor outcomes, such as the development of donor-specific antibodies or reduced estimated glomerular filtration rate. One safety issue that must be considered when using belatacept is the potential for increased risk of post-transplant lymphoproliferative disease. There were more cases of post-transplant lymphoproliferative disease in belatacept-treated patients, especially in recipients seronegative for Epstein–Barr virus or patients treated with lymphocyte-depleting agents. Therefore, belatacept can be recommended for use in Epstein–Barr virus antibody-positive recipients.Keywords: belatacept, kidney transplant, acute rejection